An approach to data collection in compassionate use/managed access - Sarp, Séverine; Reichenbach, Ramona; Aliu, Paul (Frontiers in Pharmacology, 2022)
Compassionate Use (CU)/Managed Access programs provide access to locally unapproved medicines. As these programs become more global and involve a broader range of products, determining whether patients derive benefit from treatment could provide insights into therapeutic use in a real-word setting with diverse pools of patients. CU primary purpose is to provide treatment and it is not targeting research. However, it is increasingly considered as a source of real-world data. In the absence of a harmonized framework on CU data collection, Novartis developed a company-wide guidance to collect baseline patient data and prospectively acquire information at product resupply.